FINANCIAL STRUCTURE AND PROFIT DYNAMICS SHAPING TAX AVOIDANCE IN INDONESIAN CONVENTIONAL BANKS LISTED 2020–2024 - Diansyah; Fina Dwi Apriyanti (RADJA PUBLIKA, 2026)
This study aims to examine the effect of leverage, firm size, profitability, and capital intensity on tax avoidance in conventional commercial banks listed on the Indonesia Stock Exchange during the 2020–2024 period. This study uses secondary data in the form of annual financial statements and applies a purposive sampling method, result-ing in 28 banks. The analytical technique employed is multiple linear regression using SPSS version 26. The results indicate that, partially, profitability has a significant effect on tax avoidance, while leverage, firm size, and capital intensity do not have a significant effect. However, simultaneously, leverage, firm size, profitability, and capi-tal intensity have a significant effect on tax avoidance. These findings indicate that tax avoidance practices in the banking sector are influenced by a combination of corporate financial characteristics, with profitability as the main determinant.